Pengaruh Terapi Jus Lemon Dengan Obesitas Pada Ibu Post Partum di Puskesmas Majalengka Kakabupaten Majalengka - Mardiani, Norma; Eni, Eni (UKInstitute, 2024)
Postpartum weight changes can lead to persistent obesity in some mothers, posing health risks if not addressed. This study investigates the impact of lemon juice therapy on obesity in postpartum mothers at the UPTD Majalengka Health Center, Majalengka Regency. Using a pre-experimental design with a pretest-post one-group approach, the study involved 30 postpartum mothers who were obese within 6 hours to 6 weeks after giving birth in June 2024. The total sampling method was employed, and data were analyzed using bivariate techniques. The findings revealed that after undergoing lemon juice therapy, 36.7% of the participants were classified as overweight (BMI 23-24.9), 46.6% as obese (BMI 25-29.9), and 16.7% as Obesity II (BMI ≥ 30). The statistical analysis indicated a significant effect of lemon juice therapy on reducing obesity in postpartum mothers, with a p-value of 0.000. This research highlights the potential of lemon juice therapy as an alternative treatment for managing postpartum obesity, offering valuable insights into obesity prevention and management strategies for postpartum women.